Impact of State-Offered Healthcare on the Quality of Life of the Elderly in Poland – Regional Analysis - Rozpędowska-Matraszek, Danuta; Nowak-Sapota, Kazimiera (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The article attempts to answer the question whether the employment structure of those working directly with the patient in public healthcare will ensure equal access of the elderly to appropriate healthcare in voivodships, which may improve their quality of life. Those people are a group within the society which uses medical services to a considerably larger extent. The analysis will be an introduction to a more thorough study into the impact of healthcare on the quality of life of the elderly. This article focuses only on employment which, as many economic variables, shows considerable sensitivity to changes in structure diversity. The analysis of employment in the group of seven medical professions in specific voivodships uses the Berzeg panel model as a tool to examine structural changes in social and economic phenomena, i.e. changes in employment that occur in the geographical space in a specific period of time. Based on the estimated model parameters, the impact of structural changes in medical workers’ employment in voivodships, geographical changes – in competitiveness and spatial interactions (adjacency) on changes in the regional employment of medical staff is assessed.